Advances in Computer Science and Information Technology First International Conference on Computer Science and Information Technology, CCSIT 2011, Bangalore, India, January 2-4, 2011. Proceedings, Part I - Meghanathan, Natarajan; Kaushik, Brajesh Kumar; Nagamalai, Dhinaharan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume constitutes the first of three parts of the refereed proceedings of the First International Conference on Computer Science and Information Technology, CCSIT 2010, held in Bangalore, India, in January 2011. The 59 revised full papers presented in this volume were carefully reviewed and selected. The papers are organized in topical sections on distributed and parallel systems and algorithms; DSP, image processing, pattern recognition, and multimedia; software engineering; database and data Mining; as well as soft computing, such as AI, neural networks, fuzzy systems, etc.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Algorithm Analysis and Problem Complexity; Software Engineering; Information Storage and Retrieval